A Systematic Scoping Review of the Prevalence, Etiological, Psychological, and Interpersonal Factors Associated with BDSM. Issue 6 (23rd July 2020) - Brown, Ashley; Barker, Edward D.; Rahman, Qazi
ABSTRACT: BDSM (bondage, discipline, dominance, submission, and sadomasochism) encompasses a diverse set of sexual interests. Research interests in BDSM have been historically underpinned by examining potential mental health issues, unhealthy fixations on specific sexual behaviors, and/or the presence of childhood trauma, as is predicted by psychopathological and psychoanalytic models. The objective of this scoping review was to provide an overview of the current landscape of BDSM research, including incidence rates, evidence for psychopathological, psychoanalytical, biological, and social etiological factors, demographics of BDSM practitioners, and the psychological correlates of those with BDSM interests. After the literature search and screening process, 60 articles were included. BDSM related fantasies were found to be common (40-70%) in both males and females, while about 20% reported engaging in BDSM. Results show little support for psychopathologic or psychoanalytic models. In the selected samples studied, BDSM practitioners appear to be white, well educated, young, and do not show higher rates of mental health or relationship problems. Research supports BDSM being used as a broadening of sexual interests and behaviors instead of a fixation on a specific interest. Future empirical research should focus on non-pathological models of BDSM, discrimination of BDSM practitioners, interpersonal relationships, and biological factors.